Four years of the COVID-19 pandemic: How does Brazil deal with the impacts? A DOHaD perspective - Aquino, Ariana Musa De [UNESP]; Cruz, Larissa Lopes Da; Gouveia, Henrique José Cavalcanti Bezerra; Da Silva, Márcia Maria; Souza, Maysa Rocha De [UNESP]; Baqueiro, Mayara Da Nóbrega; Ribeiro, Isabelle Tenori [UNESP]; De Lima, Emanuelle Vasconcellos; Martins, Pedro Vinicius Gonçalves; Gonçalves, Carolina Oliveira; Ceravolo, Graziela Scalianti; Miranda, Rosiane Aparecida (Cambridge University Press (CUP), 2024)
Over the last few years, during the pandemic, the Brazilian population has suffered several problems, ranging from health to socioeconomic impacts. When we consider Brazilian science, there has been an undeniable scientific delay generated by the pandemic, especially in areas that are not related to the coronavirus. In this context, with the aim of fostering collaboration among researchers in the field of Developmental Origins of Health and Diseases (DOHaD) and enhancing the potential for implementing public health strategies to prevent noncommunicable chronic diseases, the Brazilian Association of Developmental Origins of Health and Diseases (DOHaD Brazil) was established in 2020. In this narrative, we explore the effects of the COVID-19 pandemic in Brazil, focusing on its impacts on scientific research conducted in universities. Additionally, we underscore the significance of the DOHaD Brazil Association, particularly from the perspective of young researchers engaged in DOHaD research in Brazil.
Keywords: DOHaD; SARS-CoV-2; Scientific Funding; Scientific Society; South America; Universities